GC-MS ANALYSIS OF SOME PLASTIC COMPONENTS FROM 1997-2003 COMPUTER MAIN BOARDS - KOVACS, Dalma; SIMEDRU, Dorina; KOVACS, Melinda (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Recycling is one of most important steps toward circular economy. Since the quantity of waste of electrical and electronic equipment (WEEE) is increasing rapidly, it became crucial to know its composition to find adequate recycling solutions. Following this trend, the present study aims to find the major components of plastic components from 1997-2003 computer main boards. A new GC-MS method was developed and used to quantify the main volatile organic compounds of polystyrene PS (benzene, ethylbenzene), acrylonitrile butadiene styrene ABS (acetophenone, styrene, butyldiglycol) and polypropylene PP (n-Tetradecane, n-Hexadecane and n-Heptadecane). The extraction method was carried out using a saline water solution (10 % saline content; w:v) to extract the volatile compounds on SPME fibers under continuous agitation at 55 °C. The analytical method used a complex temperature program and a HP-5ms fused-silica capillary column of 30 m length × 0.25 mm I.D. × 0.25 µm film thickness (Restek, USA) to achieve separation of the compounds. The investigation of the major components of plastic components from 1997-2003 computer main boards using the developed method showed a decrease of ABS and PP major components from 1997 to 2003 and an increase of the major components from PS.